Pengaruh Social Media Marketing Activities, Brand Experience, Brand Reputation and Brand Equity Terhadap Purchase Intention Produk Uniqlo JABODETABEK - Muhammad Ridwan; Jatmiko Jatmiko (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to investigate the relationship between Social Media Marketing Activities, Brand Experience, Brand Reputation, and Brand Equity towards Purchase Intention on the brand. A survey method was employed to collect data from respondents who are customers of the brand in the JABODETABEK area. The sample consisted of 180 respondents, and Multiple Linear Regression Analysis using SPSS was utilized to test the proposed hypotheses. The data collection technique employed purposive sampling. The results of the study indicate a significant positive correlation between Social Media Marketing Activities, Brand Experience, Brand Reputation, Brand Equity, and customers' Purchase Intention. This underscores the importance for Uniqlo to address these issues through improved marketing strategies, consistency in customer experience, reputation enhancement, and efforts to build strong brand equity. Uniqlo can enhance brand awareness, strengthen interaction with potential customers, build trust, increase customer preference, and ultimately boost consumers' intention to purchase its products. The managerial implications of this research highlight the importance of enhancing Social Media Marketing Activities, strengthening Brand Experience, building a good Brand Reputation, and continuously innovating to enhance Brand Equity. These findings provide valuable insights for marketing managers in designing effective strategies to increase sales and strengthen the brand's position in the market.